Effect of pre-chilling on ovarian tissue - Teas, Emmerson; Fowler, Kate; Kuscu, Nilay; Kilbride, Peter; Williams, Suzannah (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):235